Extracellular Alkalinization as a Defense Response in Potato Cells - Moroz, Natalia; Fritch, Karen R.; Marcec, Matthew J.; Tripathi, Diwaker; Smertenko, Andrei; Tanaka, Kiwamu (Frontiers in Plant Science, 2017)
A quantitative and robust bioassay to assess plant defense response is important for studies of disease resistance and also for the early identification of disease during pre- or non-symptomatic phases. An increase in extracellular pH is known to be an early defense response in plants. In this study, we propose a fast and reliable alkalinization assay to monitor plant defense response in potatoes. Using potato suspension cell cultures, we observed an alkalinization response against various pathogen- and plant-derived elicitors in a dose- and time-dependent manner. We also assessed the defense response against a variety of potato pathogens, such as protists (Phytophthora infestans and Spongospora subterranea) and fungi (Verticillium dahliae and Colletotrichum coccodes). Our results show that extracellular pH increases within 30 min in proportion to the number of pathogen spores added. Consistently with the alkalinization effect, the higher transcription level of several defense-related genes and production of reactive oxygen species was observed. Our results demonstrate that the alkalinization assay is an effective tool to study early stages of defense response in potatoes.